2017
DOI: 10.1001/jamacardio.2017.0363
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcification and Risk of Cardiovascular Disease and Death Among Patients With Chronic Kidney Disease

Abstract: Importance Coronary artery calcification (CAC) is highly prevalent in patients with pre-dialysis chronic kidney disease (CKD). However, there are sparse data on the association of CAC with subsequent risk of cardiovascular disease (CVD) and all-cause mortality in this population. Objectives To study the prospective association of CAC with risk of CVD and all-cause mortality among patients with pre-dialysis CKD. Design, Setting, and Participants Chronic Renal Insufficiency Cohort study recruited adults aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
249
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(265 citation statements)
references
References 42 publications
7
249
1
8
Order By: Relevance
“…Such a diet is also associated with reduced lowdensity lipoprotein cholesterol (LDL-c) [17], and decreased LDL-c predicts a reduction in major CVD events in CKD [18]. Furthermore, high F + V diets are associated with reduced risk of coronary artery calcification (CAC) [19], which independently predicts CVD risk over and above more traditional CVD risk factors in the general population [20], is more common and more severe in CKD [21], and has stronger association with risk of CVD and mortality in CKD patients [22]. Vitamin K-dependent matrix Gla protein contributes to the physiologic prevention of CAC [23], and low vitamin K status common in CKD patients [24] might be corrected by increased F + V intake.…”
Section: Introductionmentioning
confidence: 99%
“…Such a diet is also associated with reduced lowdensity lipoprotein cholesterol (LDL-c) [17], and decreased LDL-c predicts a reduction in major CVD events in CKD [18]. Furthermore, high F + V diets are associated with reduced risk of coronary artery calcification (CAC) [19], which independently predicts CVD risk over and above more traditional CVD risk factors in the general population [20], is more common and more severe in CKD [21], and has stronger association with risk of CVD and mortality in CKD patients [22]. Vitamin K-dependent matrix Gla protein contributes to the physiologic prevention of CAC [23], and low vitamin K status common in CKD patients [24] might be corrected by increased F + V intake.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, recent studies have found that subclinical atherosclerosis detected as CAC is a predictor of CVD and high CV mortality in CKD patients as well as in the general population [12, 13]. However, coronary calcium scoring requires high costs, skilled expertise, and risk of radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery calcification (CAC) was recently established as a predictor of CV complications in the general population and is recommended for use in assessing CV risk in asymptomatic adults with intermediate risk [11]. Recent studies have identified CAC as a predictor of CV disease and mortality in CKD patients, suggesting the possibility of a risk prediction tool for CKD [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…This important question has been addressed recently by Chen et al [5] in JAMA Cardiology . This prospective study included adults with CKD who were dialysis-naïve.…”
Section: Is the Risk Of Vc More Related To Dialysis Or Is It Associatmentioning
confidence: 99%